POLYMORPHISM PRO12ALA OF THE PPARG-2 GENE (rs1801282) IN CHILDREN WITH OBESITY - Garifullina, Lilia; Rustamov, Uktam (Medical science of Uzbekistan, 2025)
Resume: This article presents data from a study of the Pro12Ala polymorphism of the PPARG-2 gene in obese children. The study results are recommended for widespread implementation in the practice of pediatric hospital physicians. The aim of the work: to study the frequency of the Pro12Ala polymorphism of the PPARG 2 gene in children with different types of obesity. Materials and methods: a comparative characteristic of the study of the frequency of carriage of the Pro 12 Ala polymorphism of the PPARG-2 gene in 211 children with obesity and 104 children with normal body weight was carried out. The method of molecular genetic examination was used. Results: It was revealed that the Pro 12 Pro genotype of the Pro 12 Ala polymorphism of the PPARG-2 isoform gene of the peroxisome activator gene was directly associated with the formation of obesity in children and adolescents, namely abdominal obesity. The predisposing genotype in children with AO was Pro12 Pro, and in children with abdominal obesity without metabolic disorders, the frequency of the minor allele 12Ala was statistically higher compared to children with manifestations of MS, which allows us to classify this allele as protective for the development of metabolic disorders.